Komunikasi Transaksional dalam Project Based Learning di SMA MBS Zam-Zam Muhammadiyah Banyumas - Ika Dian Nur Rizki; Musa Musa; Muridan (Advances In Education Journal, 2026)
This study evaluates the transformation of communication models from linear to transactional through the implementation of Project-Based Learning (PjBL) at SMA MBS Zam-Zam Muhammadiyah Banyumas, aimed at addressing low student motivation. Using a descriptive qualitative approach with a case study method, data were gathered through participant observation, documentation, and literature reviews of four primary projects: folklore drama performances, biography writing, book reviews, and potentialsite observations at Situ Elok. The findings reveal that PjBL implementation successfully dismantled the "sacred prison" stigma caused by the monotony of boarding school routines. The transactional model positions students as active subjects who coconstruct "shared meaning" through multidirectional interactions with teachers, the community, and local policymakers. This transformation significantly enhanced students' enthusiasm, self-confidence, and critical thinking skills by providing authentic and applicable learning experiences. In conclusion, reorienting from teacher-centered to humanistic and contextual student-centered learning is essential for effective language education in modern Islamic boarding school environments.